DEVELOPMENT OF SHARED-TYPE INTEGRATED E-MODULE WITH THEME “MOTION OF OBJECTS AND LIVING THINGS IN OUR ENVIRONMENT” FOR SECONDARY SCHOOL SCIENCE LESSON - Hilman Yusri; Monica Prima Sari (Department of Science Education, 2023)
This study aims to develop a shared-type integrated e-module with theme “Motion of objects and living things in our environment” for secondary school science lesson. Plomp model is used in this Research and Development study, which consist of three stages namely: preliminary research, prototype stage, and assessment stage. A set of questionnaires was prepared to test validity and practicality of product. Validity test was conducted involving three lecturers from Science Education department, and practicality test was conducted involving 9 students and 3 science teachers at SMPN 1 Kampar. The results of the validity test gave the value of 89.79% which belongs to highly valid category, practicality test with students gave the value of 90.74% and with teacher 93.75% which belong to highly practical.